2019
DOI: 10.1007/s42994-019-00007-9
|View full text |Cite
|
Sign up to set email alerts
|

Positional effects on efficiency of CRISPR/Cas9-based transcriptional activation in rice plants

Abstract: The nuclease-dead Cas9 (dCas9) has been reprogrammed for transcriptional activation by fusing dCas9 to a transcriptional activation domain. In the presence of a guide RNA (gRNA), the dCas9 fusions specifically bind to regions of a promoter to activate transcription. Significant amount of effort has been directed toward the identification and optimization of the fusions of dCas9-activation domain, but very little is known about the impact of gRNA target positions within a promoter in plants on transcriptional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Although the CRISPR-derived synthetic gene activators are widely useful for gene functional studies, crop improvement, and synthetic biology, the development and application of these tools in plants is substantially lagging behind that in animals (Li et al, 2020). To date, targeted gene activation in plants mostly used dCas9-TADs with multiple sgRNAs associated with the same target promoter to synergistically increase the overall transcriptional activation efficacy (Lowder et al, 2015(Lowder et al, , 2018Piatek et al, 2015;Vazquez-Vilar et al, 2016;Park et al, 2017;Lee et al, 2019;Papikian et al, 2019;Ren et al, 2019;Selma et al, 2019;Gong et al, 2020). Despite being effective, this design can increase potential off-target effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the CRISPR-derived synthetic gene activators are widely useful for gene functional studies, crop improvement, and synthetic biology, the development and application of these tools in plants is substantially lagging behind that in animals (Li et al, 2020). To date, targeted gene activation in plants mostly used dCas9-TADs with multiple sgRNAs associated with the same target promoter to synergistically increase the overall transcriptional activation efficacy (Lowder et al, 2015(Lowder et al, , 2018Piatek et al, 2015;Vazquez-Vilar et al, 2016;Park et al, 2017;Lee et al, 2019;Papikian et al, 2019;Ren et al, 2019;Selma et al, 2019;Gong et al, 2020). Despite being effective, this design can increase potential off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although several improved dCas9-TAD tools are currently available for targeted gene activation in plants, there are still issues that need to be addressed. Firstly, although efficient transcriptional activation of a single endogenous gene by dCas9-TADs in combination with multiple sgRNAs binding to the same target promoter has been repeatedly reported in transgenic plants (Lowder et al, 2015(Lowder et al, , 2018Park et al, 2017;Lee et al, 2019;Papikian et al, 2019;Ren et al, 2019;Gong et al, 2020), robust transcriptional coactivation of multiple genes by dCas9-TADs has not been demonstrated in whole plants. Secondly, it is unclear how many generations the multiplex gene activation can persist for.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the efficiency of CRISPR/Cas9 in controlling the gene expression of protein-coding and non-coding genes in Arabidopsis, additive transcription activation was observed by Lowder et al, who targeted three different sites in the promoter of the production of anthocyanin pigment1 gene (AtPAP1, encoding a transcription factor) and miR319 (encoding a microRNA; Lowder et al, 2015). Gong et al (2020) targeted two different genes, OsWOX11 and OsYUC1, involved in crown root development and auxin biosynthesis in rice, respectively. They designed multiple gRNAs to target different sites in the promoter regions upstream of these genes, and the results indicated that targeting two different regions within 350 bp upstream of the TSS is most effective for dCas9-TV-based transcriptional activation.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…The chromatin accessibility information helps to choose and design gRNAs. Recently, Gong and colleagues reported that when gRNA targeted 350 bp upstream of OsWOX11 , the edit efficiency was high (Gong et al ., 2020). We found that the reason might be due to the open chromatin feature at that region (Figure 1g).…”
Section: Figurementioning
confidence: 99%